2012
DOI: 10.1029/2012jd017710
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value of Microwave Sounding Unit–radiosonde comparisons in ascertaining errors in climate data records of tropospheric temperatures

Abstract: [1] Multidecadal-scale changes in atmospheric temperature have been measured by both radiosondes and the satellite-borne microwave sounding unit (MSU). Both measurement systems exhibit substantial time varying biases that need to removed to the extent possible from the raw data before they can be used to assess climate trends. A number of methods have been developed for each measurement system, leading to the creation of several homogenized data sets. In this work, we evaluate the agreement between MSU and hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 43 publications
(96 reference statements)
1
34
0
Order By: Relevance
“…However, its utilization is found to be quite limited in analysing global and regional warming trends [15]. For example, Microwave Sounding Units (MSU) and Advanced Microwave Sounding Units (AMSU) on NOAA satellite data have been analysed during the past several decades (i.e., 1979–2010) in comprehending warming trends over: (i) near global (i.e., ~75°S to 75°N) [1617]; (ii) tropics (i.e., ~20°S to 20°N) [1718]; (iii) northern extratropics (i.e., ~20°N to 82.5°N) [17]; and (iv) southern extratropics (i.e., (i.e., ~82.5°S to 20°S) [17]. Despite the importance of these studies, the MSU/AMSU-derived data has limited use in local warming trend analysis because of their coarse spatial resolution (i.e., 2.5° x 2.5°).…”
Section: Introductionmentioning
confidence: 99%
“…However, its utilization is found to be quite limited in analysing global and regional warming trends [15]. For example, Microwave Sounding Units (MSU) and Advanced Microwave Sounding Units (AMSU) on NOAA satellite data have been analysed during the past several decades (i.e., 1979–2010) in comprehending warming trends over: (i) near global (i.e., ~75°S to 75°N) [1617]; (ii) tropics (i.e., ~20°S to 20°N) [1718]; (iii) northern extratropics (i.e., ~20°N to 82.5°N) [17]; and (iv) southern extratropics (i.e., (i.e., ~82.5°S to 20°S) [17]. Despite the importance of these studies, the MSU/AMSU-derived data has limited use in local warming trend analysis because of their coarse spatial resolution (i.e., 2.5° x 2.5°).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade many studies based on MSU/ AMSU observations have shown that the tropical tropospheric temperature increases more than the surface temperature on multidecadal time scales (Fu et al 2004;Fu and Johanson 2005;Mears andWentz 2005, Thorne et al 2007;Santer et al 2008), while others suggest reduced tropospheric warming relative to the surface (e.g., Christy et al 2007Christy et al , 2010Douglass et al 2008). Our understanding of tropical tropospheric temperature trends is complicated by the fact that tropical radiosonde stations are limited in number, their trends are cold biased, and the bias magnitude cannot be accurately determined (e.g., Sherwood et al 2005;Randel and Wu 2006;Titchner et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Three research teams, including the University of Alabama in Huntsville (UAH), Remote Sensing Systems (RSS), and the National Oceanic and Atmospheric Administration (NOAA) Center for Satellite Applications and Research (STAR), have developed up-to-date, homogenized datasets for the temperature of the middle troposphere (TMT) (Christy et al 2003;Mears et al 2003;Zou and Wang 2011). These groups employ over 30 years of temperature measurements from MSU and, starting in 1998, AMSU.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations